(3NhGU GdfHGJs - (3YHO GdZfj Hf CHj SQMGf Hf eSYhO GdGRehQjs
(3ChdgG (B:s
(3gPG GdHGH aj TQM COhjI HGddSGf GdjhfGfj hGdSQjGfj hGdaGQSj, hGdYLej LeYJ Pdc aj gPg GdebGdI Ydi MSH WGbJi hSYj hQJHJ Pdc Ydi MQha GdeYLe s
(3BNQgG (B:s
(3gfG GfJgi Gdbhd aj GdHGH GdNGeS YTQ, aj TQM eG hbY ef GdCOhjI GdeaQOI ef gPG GdcJGH s
(3Vef eLehY , JQJjHgG (B: (3ef U (B186 - (3U(B200s
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B88 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdNRGfI GdYGeI HGdQHGW (B((3O (B3/1363) s
Keywords: (3GdWHs